ASAS KEPATUTAN DALAM PEMBERIAN GANTI RUGI DAN KOMPENSASI OLEH PT. PERUSAHAAN LISTRIK NEGARA (PERSERO) ATAS TANAH MASYARAKAT (Studi pada Pembangunan Jaringan Kabel Saluran Udara Tegangan Ekstra Tinggi (SUTET) di Kabupaten Langkat dan Kota Binjai) - Marasamin Ritonga; Ningrum Natasya Sirait; Tan Kamello; Mahmul Siregar (USU LAW JOURNAL, 2016)
Based on the legal handling on the compensation for the people who were harmed by the construction of SUTET Cable Network which was resulted in the agreement by both parties (PT. PLN (Persero) and the people), followed by the opinion of the District Attorney, it could be concluded that: The principle of compatibility played an important role in determining the achievement and the application of justice and certainty as the responsibility of the stakeholders for their performance and willingness to comply with their agreement. The process of the principle of compatibility through the agreement by reconciliation as the realization of the living custom with transparency and consanguinity could set aside the policy of the Decree of the Minister of Mining and Energy No. 975 K/47/MPE/1999. In maximizing its function and responsibility, PT. PLN (Persero) should admit that economic development is more advanced than the written record. In order not to be long-winded in the concept of compensation, it is necessary to be brave enough in internal improvement in prioritizing the need for justice and the need for legal certainty so that the goal is more prioritized than the procedure in taking the responsibility   Keywords: Principle of Compatibility, Compensation, Justice